Liberia’s Post-1990 Ecomog Incursion: An Assessment of Anglophone – Francophone Dichotomy (Journal of International Studies, 2017)
One of the successful stories of regional economic communities (RECs) today is that of the Economic Community of West African States (ECOWAS). Founded in 1975, it is a conglomeration of states having similar but distinctively different colonial experiences in West Africa; the Anglophone, the Francophone and the Lexiphone. Contemporary political events in the world had made ECOWAS flexible and receptive to reforms. Although there was little internal wrangling within the ECOWAS member states, because of the transformation and expansion of the economic bloc’s re-establishing, its grasps over political, security and social events within the sub-region after the cold war, the development brought division in ECOWAS, and expressed such in the form of Anglophone and Francophone dichotomy, for reason of not agreeing to military intervention. The ECOWAS shift from non-interference principles to military intervention was noticeable when ECOMOG intervened in Liberia’s 1990 internal conflict; thereby changing her non-interference posture to that of collective security action as an alternative in the sub-region. This paper attempted to establish the shift in ECOWAS security paradigm, leading to a division within ECOWAS member states along ‘linguistic lines’ and how this division affected ECOWAS in the post-Liberian intervention. Additionally, it x-rayed the nature, manifestation and consequences of such dichotomy. The paper recommended a policy option for ECOWAS to guard against future distractions among the member states in order not to divert ECOWAS from achieving her goals of economic integration.